Interactive Demonstration Learning to Improve Conceptual Understanding of Class VII Students Materials: Temperature, Heat, and Expansion - Trisni, Nurila; Syahril, Syahril; Fauza, Naila (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
Science education is a great opportunity to create a generation of people with character. In classroom learning, there are several obstacles so that students do not optimally accept concepts or experience misconceptions. This situation proves that a learning process is needed that can overcome this problem. The aim achieved is to determine the effect of learning using the Interactive Demonstration model on increasing understanding of the concepts of class VII students in the material of temperature, heat, and expansion. Quasi Experiment is the method used and the design refers to Posttest-Only Control Design. The posttest results for conceptual understanding in the experimental class were superior to the results obtained in the control class. So, we can conclude that understanding the concepts of temperature, heat, and expansion in class VII at SMPN 20 Pekanbaru can be improved through the application of the Interactive Demonstration model.